Zwitterionic disilanylium from an unsymmetrical disilene - Bisai, Milan Kumar; Ajithkumar, V. S.; Raj, K. Vipin; Vanka, Kumar; Gonnade, Rajesh G.; Sen, Sakya S. (Chemical Communications, 2023)
The reaction of PhC(NtBu)2SiSi(SiMe3)(3) (1) with Me3SiCH(2)Cl afforded an unsymmetrical sp(2)-sp(3) disilene, 2, with concomitant elimination of Me3SiCl. The analogous reaction with PhC(NtBu)2SiCl resulted in the oxidative addition of the C-Cl bond at the Si(II) atom (3). The reactions of 2 with sulfur and selenium led to compounds with Si=E (E=S (4) and Se (5)) double bonds. Tellurium reacted differently with 2 and furnished a zwitterionic compound, 6.